2022
DOI: 10.31538/ndh.v7i3.2678
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Leadership and Psychological Empowerment on Employee Performance

Abstract: This article aimed to examine and analyze the effect of Spiritual Leadership and Psychological Empowerment on Employee Performance. Respondents were leaders or employees at YPPBU (Bahrul Ulum Islamic Boarding School Foundation) Jombang, totalling 64 respondents. Data were analyzed using Partial Least Square (PLS) with SmartPLS software version 3.0 and the relationship between variables. The results showed that Spiritual Leadership had no significant effect on Employee Performance (T Statistics: 0.925, P Values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It suggests that leadership effectiveness could be better understood by exploring the interplay between leaders and followers, rather than viewing them as distinct entities. In this regard, future research should not only focus on personal traits like followers’ CSE but also investigate how work tasks and other prospective organizational contexts may either complement or supplement humble leadership [ 85 , 86 ]. Future research on humble leadership should include the incorporation of such contingency variables.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that leadership effectiveness could be better understood by exploring the interplay between leaders and followers, rather than viewing them as distinct entities. In this regard, future research should not only focus on personal traits like followers’ CSE but also investigate how work tasks and other prospective organizational contexts may either complement or supplement humble leadership [ 85 , 86 ]. Future research on humble leadership should include the incorporation of such contingency variables.…”
Section: Discussionmentioning
confidence: 99%
“…Compensation methods according to Herman Sofyandi (2013) include the ranking method, job grading method, factorcomparison method, and point system method. These four methods can be used by a company to provide compensation to its employees (Rahmatika et al, 2022;Sudarman, 2021).…”
Section: Implementation Of Islamic Boarding School-based Private Mts ...mentioning
confidence: 99%
“…Specifically, we posit that spiritual leadership enhances proactive customer service performance through its impact on employees' psychological empowerment, which refers to individuals' perceptions of their control over work and the resources necessary to complete it, as well as their sense of meaning and purpose in their work (Spreitzer, 1995). psychological empowerment has been shown to positively affect proactive customer service performance in prior research (Rahmatika et al, 2022;Zhang and Begley, 2011). Research has found that spiritual leadership enhances employees' self-efficacy (Usmanova et al, 2021), it can also influence psychological empowerment because both self-efficacy and psychological empowerment are related to belief in one's capability to influence outcomes.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%